Penerapan Marketing Berbasis Online dalam Meningkatkan Omset Usaha pada UKM Karya Cipta Lestari di Desa Wonosari Kabupaten Deli Serdang - Zulfikar Sembiring; Susilawati Susilawati; Yudi Daeng Polewangi (Universitas Medan Area, 2021)
Small and Medium Enterprises have a big enough role for the welfare of society. This sector is able to absorb a large enough workforce and provide opportunities for SMEs to develop and compete with companies that tend to use large capital (capital intensive). The purpose of this activity is to improve aspects of marketing management that have an impact on increasing sales. The object of this activity is the clay pottery ceramics business in Wonosari Village, Tanjung Morawa District, Deli Serdang Regency. The main problem for partners is that partners do not focus too much on marketing management, relying more on conventional marketing systems such as ordering goods, safekeeping at the nearest store, and selling in their own stores whose position is not too strategic, causing stagnant product sales. The proposed solution is to apply management and marketing techniques for partner products using internet media such as websites and social media. The output targets of this partnership program are: 1) increasing understanding of the importance of technology to business; 2) capacity building in internet technology management; 3) increase in market absorption; 4) Improved communication skills for partners in managing websites and Social Media Marketing, namely the ability of partners to communicate products and product brands so that they have a list of regular customers on the website who have the potential to purchase products on an ongoing basis; 5) increase in partner sales turnover.